2012
DOI: 10.3354/dao02536
|View full text |Cite
|
Sign up to set email alerts
|

Piscine myocarditis virus (PMCV) in wild Atlantic salmon Salmo salar

Abstract: Cardiomyopathy syndrome (CMS) is a severe cardiac disease of sea-farmed Atlantic salmon Salmo salar L., but CMS-like lesions have also been found in wild Atlantic salmon. In 2010 a double-stranded RNA virus of the Totiviridae family, provisionally named piscine myocarditis virus (PMCV), was described as the causative agent of CMS. In the present paper we report the first detection of PMCV in wild Atlantic salmon. The study is based on screening of 797 wild Atlantic salmon by real-time RT-PCR. The samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…However, after only finding PMCV in 2 of 797 wild salmon sampled from fjords all over Norway, Garseth et al (2012) concluded that no strong link exists between PMCV in wild and farmed salmon. The isolate found in smelt was subsequently shown to be a genotype distinct from the one in salmon (Tengs & Böckerman 2012), which together with the absence of PMCV in the other wild fish species tested makes it less likely that wild fish play an important role as a reservoir for PMCV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, after only finding PMCV in 2 of 797 wild salmon sampled from fjords all over Norway, Garseth et al (2012) concluded that no strong link exists between PMCV in wild and farmed salmon. The isolate found in smelt was subsequently shown to be a genotype distinct from the one in salmon (Tengs & Böckerman 2012), which together with the absence of PMCV in the other wild fish species tested makes it less likely that wild fish play an important role as a reservoir for PMCV.…”
Section: Discussionmentioning
confidence: 99%
“…Haugland et al (2011) also succeeded in reproducing CMS in fish infected with the virus grown in cell culture, thereby establishing PMCV as the causal agent of CMS by fulfilling Koch's postulates. Since the identification of the infectious agent, PMCV has been found in wild Atlantic salmon and smelt Argentina silus (Böcker-man et al 2011, Garseth et al 2012. Now that the causal agent has been established, the lack of knowledge of potential risk factors for introduction of PMCV and outbreak of CMS has become even more evident.…”
Section: Introductionmentioning
confidence: 99%
“…), Chile (Godoy et al . ) and Canada (K. Miller, unpublished data), but whether the virus alone can cause the disease is still under debate (Garseth, Biering & Tengs ; Garver et al . ).…”
Section: Virusesmentioning
confidence: 99%
“…PMCV is the causative agent of cardiomyopathy syndrome (CMS), which causes inflammatory heart disease, primarily in farmed and wild Atlantic salmon (Salmo salar L.) [5,7,16,19]. The disease was first detected in Norway in 1985 and later was diagnosed in farmed Atlantic salmon in the Faeroe Islands in Scotland and in British Columbia, Canada [1,2,12,13].…”
Section: Introductionmentioning
confidence: 99%